The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1109/tip.2017.2700765
|View full text |Cite
|
Sign up to set email alerts
|

Joint Source-Channel Coding of JPEG 2000 Image Transmission Over Two-Way Multi-Relay Networks

Abstract: Abstract-In this paper, we develop a two-way multi-relay scheme for JPEG 2000 image transmission. We adopt a modified time-division broadcast (TDBC) cooperative protocol, and derive its power allocation and relay selection under a fairness constraint. The symbol error probability of the optimal system configuration is then derived. After that, a joint source-channel coding (JSCC) problem is formulated to find the optimal number of JPEG 2000 quality layers for the image and the number of channel coding packets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Also when the redundancy of images is utilized in the decoding process, errors can be reduced [7]. In [8], the use of JSCC in JPEG2000 transmission over a two-way relay network is studied; while in [9], [10], the applications of JSCC schemes to wireless video transmissions are investigated. In [11], an iterative joint source-channel decoder is proposed, where messages are exchanged between the decoder of variable length (source) codes (VLC) and the decoder of recursive systematic convolutional codes or low-density parity-check (LDPC) codes.…”
Section: Introductionmentioning
confidence: 99%
“…Also when the redundancy of images is utilized in the decoding process, errors can be reduced [7]. In [8], the use of JSCC in JPEG2000 transmission over a two-way relay network is studied; while in [9], [10], the applications of JSCC schemes to wireless video transmissions are investigated. In [11], an iterative joint source-channel decoder is proposed, where messages are exchanged between the decoder of variable length (source) codes (VLC) and the decoder of recursive systematic convolutional codes or low-density parity-check (LDPC) codes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the joint source-channel coding (JSCC) system has drawn increasing attention through effective utilization of the residual redundancy. The JSCC system have good error-correcting performance [2], complexity [3], [4] and transmission delay [5], and these advantages promote the JSCC system for applications in image processing [6], video transmissions [7] and so on. The JSCC system, where one low-density parity-check (LDPC) code [8] is used for source compression and one LDPC code is used for channel error correction, was proved to perform well in practical applications by utilizing the joint Tanner graph on the decoder side, named the double LDPC (D-LDPC) JSCC system [2].…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm offers 10X or higher speed compared to the previous algorithms with a slight sacrifice in the coding efficiency. In order to optimize JPEG-2000 for image transmission through wireless networks, Joint Source-Channel Coding (JSCC) has been proposed in [14] and congestion control for interactive applications over SDN networks has been proposed in [15]. Further detailed study of rate-distortion optimization for JPEG-2000 is found in [16], [17].…”
Section: Introductionmentioning
confidence: 99%